Secretion Stimulates Intramembrane Proteolysis of a Secretory Granule Membrane Enzyme - Rajagopal, Chitra (American Society for Biochemistry and Molecular Biology, 2010)
Regulated intramembrane proteolysis, a highly conserved process employed by diverse regulatory pathways, can release soluble fragments that directly or indirectly modulate gene expression. In this study we used pharmacological tools to identify peptidylglycine α-amidating monooxygenase (PAM), a type I secretory granule membrane protein, as a γ-secretase substrate. PAM, an essential enzyme, catalyzes the final step in the synthesis of the majority of neuropeptides that control metabolic homeostasis. Mass spectroscopy was most consistent with the presence of multiple closely spaced NH(2) termini, suggesting that cleavage occurred near the middle of the PAM transmembrane domain. The luminal domains of PAM must undergo a series of prohormone convertase or α-secretase-mediated cleavages before the remaining transmembrane domain/cytosolic domain fragment can undergo a γ-secretase-like cleavage. Cleavage by γ-secretase generates a soluble fragment of the cytosolic domain (sf-CD) that is known to localize to the nucleus. Although PAM sf-CD is unstable in AtT-20 corticotroph tumor cells, it is readily detected in primary rat anterior pituitary cells. PAM isoform expression, which is tissue-specific and developmentally regulated, affects the efficiency with which sf-CD is produced. sf-CD levels are also modulated by the phosphorylation status of the cytosolic domain and by the ability of the cytosolic domain to interact with cytosolic proteins. sf-CD is produced by primary rat anterior pituitary cells in response to secretogogue, suggesting that sf-CD acts as a signaling molecule relaying information about secretion from the secretory granule to the nucleus.